Efektivitas Penerapan Strategi Pembelajaran Ekspositori dalam Meningkatkan Kualitas Hafalan Al-Qur’an Siswa di Sekolah Dasar - Yesi Delfianti; Zainal Asril; Muhammad Zalnur (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This study aims to describe in depth the planning, implementation, supporting and inhibiting factors, and evaluation of the application of expository learning strategies in improving the quality of students' memorization of the Qur'an at Adzkia 1 Padang Integrated Islamic Elementary School. This research uses qualitative methods through a descriptive approach, the type of research used is field research. The results showed that Adzkia 1 Padang Integrated Islamic Elementary School has designed the implementation of learning in stages, starting from preparation, opening activities, core activities (including murajaah together and memorization deposits), to closing activities. Some of the supporting factors for the successful implementation of expository strategies include a conducive learning environment, grouping students based on ability, and choosing strategies that are considered easier for teachers and students. However, there are also some inhibiting factors such as boredom in learning, lack of independent murajaah, and lack of cooperation with parents. Thus, learning evaluation is carried out regularly through mutabaah books, weekly evaluations, and comprehensive exams. The evaluation results show an increase in the quality of memorization of the Qur'an in most students.